Tantangan Sumber Daya Manusia dalam Penyusunan LaporanKeuangan Pada Entitas Syariah Non Bank - Nur Akifa Akifa; Nindi Astuti Nindi; Akmal Akmal; Masyhuri Masyhuri (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
Human resources (HR) play a very important role in the preparation of financial statements in non-bank Islamic entities. However, in practice, there are still various challenges that can affect the quality and reliability of the resulting financial reports. This article aims to examine various HR challenges in the preparation of financial statements in non-bank Islamic entities, particularly those related to competence, understanding of Islamic accounting principles, ability to operate information technology, and compliance with applicable regulations. The method used in this article is a literature review by examining various relevant literature, journals, and regulations. The results of the study show that the limited number of personnel with Islamic accounting competence, the lack of continuous training, the rapid development of technology, and regulatory changes are the main challenges faced by non-bank Islamic entities. In addition, low understanding of Islamic financial reporting standards also has the potential to cause errors in the recording and presentation of financial statements. Therefore, efforts are needed to improve the quality of human resources through education, training, professional certification, and strengthening of the supervision system so that the resulting financial statements are more accurate, transparent, and in accordance with sharia principles.